54 Patient Satisfaction During A Pandemic – Virtually Impossible?. (4th May 2021) - Harrington, B; Keenan, R; Aboelmagd, M; O'Malley, K; Galvin, D; Hegarty, N; Connolly, S
Abstract: Introduction: Throughout the COVID-19 pandemic we conducted virtual urology clinics for the first time at our institution. We aimed to assess patient satisfaction with the virtual clinic format. Method: Patients who underwent virtual consultation were contacted by phone and surveyed about their appointment. Convenience, thoroughness, satisfaction, preference and reason for appointment were assessed via questionnaire Results: 77 randomly selected patients were contacted. 63 males (82%), 14 females (18%). Median age 61 years (range 16–86). 62 (80%) reviews, 12 (16%) new referrals, and 3 (4%) post-operative patients were surveyed. 55 (71%) were booked for repeat appointment, 13 (17%) for further investigations, 6 (8%) discharged, and 3 (4%) listed for surgery. 73 (95%) found it convenient, 3 (4%) were neutral and 1 (1%) found it inconvenient. 74 (96%) felt thoroughly assessed and 76 (99%) of patients had all their concerns addressed. 74 (96%) were satisfied with their review, 2 (3%) were neutral, and 1 (1%) was dissatisfied. Going forward, 50 (65%) would prefer virtual follow-up and 27 (35%) would prefer an in-person review. Conclusions: Virtual clinic is preferable to the majority of patients in our urology service and is deemed convenient, thorough and satisfactory by them. It should be facilitated going forward in appropriately selected patients.